A forecasting the consumer price index using time series model - Shynkarenko, Larysa; Shinkarenko, Volodymyr; Hostryk, Alexey; Dolinskyi, Leonid (My University, 2021)
This article examines the behavior of the consumer price index in Ukraine for the period from January 2010 to September 2020. The characteristics of the initial time series, the analysis of autocorrelation functions made it possible to reveal the tendency of their development and the presence of annual seasonality. To model the behavior of the consumer price index and forecast for the next months, two types of models were used: the additive ARIMA*ARIMAS model, better known as the model of Box-Jenkins and the exponential smoothing model with the seasonality estimate of Holt-Winters. As a result of using the STATISTICA package, the most adequate models were built, reflecting the monthly dynamics of the consumer price index in Ukraine. The inflation forecast was carried out on the basis of the Holt-Winters model, which has a minimum error.
Shinkarenko Volodymyr А forecasting the consumer price index using time series model / Volodymyr Shinkarenko, Alexey Hostryk, Larysa Shynkarenko, Leonid Dolinskyi // SHS Web of Conferences : 9th International Conference on Monitoring, Modeling & Management of Emergent Economy (M3E2, 2021), 2021. - Vol. 107, № 10002. – P. 1-6. https://doi.org/10.1051/shsconf/202110710002
Keywords: forecasting; consumer price index; time; series model